Combined umbilical cord blood and bone marrow from HLA‐identical sibling donors for hematopoietic stem cell transplantation in children with hemoglobinopathies. Issue 9 (7th May 2014) - Soni, Sandeep; Boulad, Farid; Cowan, Morton J; Scaradavou, Andromachi; Dahake, Jueeli; Edwards, Sandie; Walters, Mark C.
<x xml:space="preserve">Abstract</x> Background It is well established that umbilical cord blood and bone marrow are biologically different stem cell sources. Patients and Methods We analyzed the feasibility and outcome of hematopoietic stem cell transplantation (HSCT) in 13 children (median age 5.9 years) with hemoglobinopathies after the co‐ infusion of cord blood (CB) and bone marrow (BM) from the same human leucocyte antigen (HLA) identical sibling donor. We also compared outcomes of children with co‐transplantation to outcomes in children with hemoglobinopathies who had received a BM (n = 21) or CB (n = 22) transplant alone. Results Compared to CB transplant (CBT) recipients, the co‐transplant group had more rapid neutrophil (17 vs. 25 days, P = 0.013) and platelet (29 vs. 48 days, P = 0.009) recovery and less transplant related mortality. Patients who received a co‐transplant had a lower incidence of ≥grade II acute (0% vs. 26.3%) and chronic (0% vs. 21%) graft versus host disease (GVHD) compared to BM transplant (BMT) recipients (P = 0.055 and 0.045, respectively). With a median follow‐up of >60 months in each treatment group, the 5‐year probability of event free survival (EFS) was 100% in the co‐transplant group, 90% after BMT and 86% after CBT (P = 0.42). Conclusion Co‐transplantation of CB and BM from HLA‐identical sibling donors appears to be a feasible and effective strategy to further optimize outcomes of HSCT for hemoglobinopathies. Pediatr Blood Cancer 2014;61:1690–1694. © 2014 Wiley Periodicals, Inc.